Life, loss, and puffins : a novel - Hyde, Catherine Ryan (Lake Union Publishing, 2024)
"Freakishly smart. That's the unwelcome box Ru Evans is put into for life. After all, she taught herself euclidean geometry at age seven, has an eidetic memory, and is about to enter college at thirteen years old. Boarding at a house near campus 150 miles from home, Ru meets seventeen-year-old Gabriel, an outsider himself who, like Ru, has trouble making friends--until they form a fast sibling-like bond. Finding a relatable someone in the world to talk to is a first for both of them. But when Ru's mother dies and the threat of living with her miserable aunt looms, Ru hatches an escape. It's an impulsive road trip that takes Ru and Gabriel from California to Canada, where Ru can fulfill her ultimate dream: to see Atlantic puffins in the glorious wild. Mile by mile, Ru discovers the joy of friendship, found family, dark night skies, and the aurora borealis, and she basks in going from being a smart person to just a person. Though she knows they'll be in trouble when they're caught, for the short time they are navigating twist by twist of an unknown road, the freedom is liberating, and she is living for what feels like the first time." --